2017
DOI: 10.1186/s12885-017-3260-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and prognostic implications of psychological distress in patients with gastric cancer

Abstract: BackgroundThe aim of this study was to investigate the prevalence and prognostic significance of psychological distress in gastric cancer patients.MethodsThe study population included 229 gastric cancer patients visiting Yonsei Cancer Center between November 2009 and March 2011. The distress was measured by available tools including the Modified Distress Thermometer (MDT), Hospital Anxiety and Depression Scale (HADS), and Center for Epidemiologic Studies–Depression Scale (CES-D). Patients with psychological di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
112
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(129 citation statements)
references
References 24 publications
5
112
4
1
Order By: Relevance
“…This could underline that the intensity of fear is not linearly associated with the “objective danger” the individual is in. Results from other studies are mixed, but none have reported a higher risk for being in distress in stage I compared with stage II or III …”
Section: Discussionmentioning
confidence: 87%
“…This could underline that the intensity of fear is not linearly associated with the “objective danger” the individual is in. Results from other studies are mixed, but none have reported a higher risk for being in distress in stage I compared with stage II or III …”
Section: Discussionmentioning
confidence: 87%
“…It appears important to target EC in psychosocial interventions in the early cancer pathway to decrease the anxiety and depression symptoms of patients. This seems particularly essential for gastric and esophageal cancer patients who report a high preoperative and postoperative prevalence of emotional distress and poor survival rates . Moreover, emotional distress is associated with a poorer survival in gastric cancer patients related to treatment noncompliance .…”
Section: Discussion‐conclusionmentioning
confidence: 99%
“…This seems particularly essential for gastric and esophageal cancer patients who report a high preoperative and postoperative prevalence of emotional distress and poor survival rates . Moreover, emotional distress is associated with a poorer survival in gastric cancer patients related to treatment noncompliance . Interventions based on EC can improve EC and its beneficial effects .…”
Section: Discussion‐conclusionmentioning
confidence: 99%
“…Sephton et al (2009) found that the more depressive symptoms in women with BC, the higher immunosuppression was. Similarly, Kim et al (2017) found that the presence of psychological problems correlated with lower survival than the absence of said issues in patients with stages I-III gastric cancer (60% vs. 76%, respectively). Additionally, emotional distress in patients with cancer may confer a worse prognosis (Rieke et al, 2017) since, as distress increases, coping deteriorates, therapeutic compliance worsens (Conley, Bishop, & Andersen, 2016;Greer, Pirl, Park, Lynch, & Temel, 2008), and the risk of disease progression or recurrence grows (Pinquart & Duberstein, 2010;Satin, Linden, & Phillips, 2009).…”
Section: Discussionmentioning
confidence: 86%